Implementasi Kepemimpinan Manajerial Grid Terhadap Inovasi Pembelajaran di SMP IT Utsman Bin Affan Surabaya - Nur Farahana, Kharisma; Tri Hapsari, Chelsea; Maeizy Hamdi Bajeber, Shakira; Nuril Hidayah, Farisa; Azlinatul Zulfa, Nur; Roesminingsih, Erny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the principal's implementation of Managerial Grid leadership on learning innovation at SMP IT Utsman Bin Affan Surabaya. The research is motivated by the importance of principal leadership in balancing task-oriented and people-oriented orientations to support sustainable learning innovation. This study used a qualitative approach with a case study. Data collection techniques included in-depth interviews, observation, and documentation. The results indicate that the principal implemented Managerial Grid leadership with a strong task orientation through systematic program planning, continuous evaluation, structured supervision, and effective resource management. Furthermore, the people orientation was manifested through a family approach, strengthening motivation, teacher professional development, and a structured reward system. This leadership implementation had a positive impact on learning innovation. Overall, the principal's leadership pattern demonstrates Team Management characteristics (9.9) in Managerial Grid theory because it is able to balance high attention to tasks and human relationships.